The Inarticulate Renaissance : Language Trouble in an Age of Eloquence - Mazzio, Carla, 1965- (Book collections on Project MUSE., 2009)
The Inarticulate Renaissance explores the conceptual potential of the disabled utterance in the English literary Renaissance. What might it have meant, in the sixteenth-century "age of eloquence," to speak indistinctly; to mumble to oneself or to God; to speak unintelligibly to a lover, a teacher, a court of law; or to be utterly dumfounded in the face of new words, persons, situations, and things? This innovative book maps out a "Renaissance" otherwise eclipsed by cultural and literary-critical investments in a period defined by the impact of classical humanism, Reformation poetics, and the flourishing of vernacular languages and literatures.For Carla Mazzio, the specter of the inarticulate was part of a culture grappling with the often startlingly incoherent dimensions of language practices and ideologies in the humanities, religion, law, historiography, print, and vernacular speech. Through a historical analysis of forms of failed utterance, as they informed and were recast in sixteenth-century drama, her book foregrounds the inarticulate as a central subject of cultural history and dramatic innovation. Playwrights from Nicholas Udall to William Shakespeare, while exposing ideological fictions through which articulate and inarticulate became distinguished, also transformed apparent challenges to "articulate" communication into occasions for cultivating new forms of expression and audition.